KITAB SANJATA MU'MIN - Wardatun Nadhiroh (SUHUF, 2018)
Among the Banjar people, the book of Sanjata Mu'min has been guidance to everyday life. Various readings and prayers derived from the verses of the Qur'an in this book are believed to have certain efficacies. Like the weapons used to guard against opponents' attacks, the practices of the Sanjata Mu'min are intended as such. It is interesting to study this book to know how the Banjar people construct the concept of weapons and how their religious rationality forms an identity that is only owned by the Banjar people. Through phenomenological approach, this study concluded that the Banjar people prefer to depend on the Qur'anic verses and other Islamic recitation than previously magical objects to reach their concept of ideal prosperous life, both in the world and the hereafter. The merit of the recitation in the Sanjata Mu'min believed by the Banjar people is a manifestation of lay exegesis of the Qur'anic verses through their semantic-functional reception.